ISLAMIC BUSINESS ETHICS DALAM MENINGKATKAN PROFITABILITAS HARIS ISTANA PARFUM - Ahmadi; Kholifah (Al-Idarah, 2025)
Islamic business ethics is a set of moral principles that distinguish between good and bad in a business activity in Islam. By adhering to this foundation, every Muslim who does business will feel the presence of a third party (God) in every aspect of his life. This study aims to determine the concept and application of Islamic business ethics for Haris Istana Parfum employees, which then makes the researcher interested in conducting further research on business ethics applied at Haris Istana Parfum to increase profitability as much as possible. The focus of the researcher of this study is to describe Islamic business ethics in increasing profitability in the Haris Istana Parfum shop in Randegan Village, Mojokerto, in order to know how Islamic business ethics are applied in Haris Istana Parfum, and to analyze Islamic business ethics in increasing profitability in Haris Istana Parfum. This study uses a descriptive qualitative method conducted by observation, documentation and direct interviews with business owners, employees and consumers of Haris Istana Parfum. This study is intended to describe or explain certain conditions and symptoms that occur in Haris Istana Parfum in detail, as well as to provide a general overview of the application of Islamic business ethics in Haris Istana Parfum which is then reconstructed or updated to be in accordance with the theories of Islamic business ethics. The results of this study are that the application of Islamic business ethics carried out by Haris Istana Parfum is in accordance with the theories of Islamic business ethics which result in increased profitability received by the high results or profits obtained by Haris Istana Parfum. The implementation of Islamic business ethics includes the principles: divinity, justice, free will, and responsibility.